„Bo to jej udało się uciec” – droga do emancypacji Josephine w komiksie Fatale Eda Brubakera i Seana Phillipsa - Srul, Klaudia (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The author comprehensively analyzes the construction of the character of Josephine – the protagonist of the comic book series Fatale (2012–2014). Based on it, she draws conclusions regarding the protagonist’s subjectivity, the image of the family created on the pages of comic book history, and the gradual development of the heroine’s agency. The author shows that all these elements contribute to Josephine’s emancipation, which takes place in the series finale.